ACCOUNTING RISKS AND THEIR IMPACT ON BUSINESS SUSTAINABILITY AMID GEOPOLITICAL UNCERTAINTY IN THE MIDDLE EAST: AN ANALYTICAL CONCEPTUAL STUDY - Hamza N. Aljumaili; Eko Sudarmanto; Hikmahwati; Hesty Erviani Zulaecha (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study examines the impact of accounting risks on business sustainability amid geopolitical uncertainty in the Middle East. It aims to develop a conceptual framework that links geopolitical instability to key accounting risks namely measurement, disclosure, fraud, and non-compliance and assesses their effects on sustainability dimensions: economic, social, environmental, and governance. The research adopts a conceptual analytical methodology, relying on a comprehensive literature review of academic sources and institutional reports. It identifies how geopolitical events such as conflicts, sanctions, and regulatory shifts exacerbate accounting risks and distort financial information, undermining effective decision-making and stakeholder trust. The findings reveal that geopolitical uncertainty significantly intensifies accounting risks, leading to reduced reporting reliability, impaired governance, and weakened long-term business viability. The study highlights the mediating role of accounting information quality in either amplifying or mitigating these effects. Key recommendations include enhancing risk management systems, improving transparency through integrated reporting, strengthening governance frameworks, and tailoring accounting standards to the region’s unique geopolitical context. The study emphasizes the importance of resilient accounting practices as a foundation for sustainable business operations in volatile environments.